El rol del empowerment en el éxito empresarial - Cálix, Carlos Geovany (2016)
Business success is based on having successful strategic objectives and an adequate corporate culture that embraces the values of the company, the organizational climate, the management style and the implementation of various administrative tools. Therefore, the aim of the present study is to analyze if the business success can be explained from the empowerment as a management tool, in addition to a set of individual variables of each company, such as: age, size and level of earned income. In this regard, we have worked with your own database that gathers information from Honduran enterprises. Based on the theory of resources and capabilities, were applied econometric models as probit and ordinal probit. The results are consistent and show that the empowerment is a significant variable of business success as well as the variables: age, size and level of earned income. The present work is relevant given that allows you to apply certain considerations in the business field linked with the central objective to promote success in the business. The main obstacle lies in the characterization and size of the sample.